A review of the fixed dose use of new oral anticoagulants in obese patients: Is it really enough? - Güler, Ekrem; Güler, Gamze Babür; Demir, Gültekin Günhan; Hatipo?lu, Suzan (AVES, 2015)
Obesity is a significant cause of morbidity and mortality, and it is becoming increasingly prevalent worldwide. Altered pharmacodynamics and pharmacokinetics of drugs in obese patients require dose adjustment according to body weight. New oral anticoagulants (NOACs), which are more frequently used for anticoagulation, are recommended to be used at a fixed dose based on data derived from phase 2 and 3 studies. However, the representation of obese patients [>100 kg or a body mass index (BMI) of >30 kg/m] in subgroups with a small sample size and reports of various emboli cases under drug treatment have raised suspicions about the adequacy of fixed dose use. To address this issue, we analyzed several patients with a body weight of >100 kg or BMI of >30 kg/m participating in NOAC studies and evaluated whether these numbers were sufficient to enable an accurate recommendation of fixed dose use in obese patients.
Keywords: Obesity; Anticoagulants; Factor xa Inhibitor; Dabigatran; Oral; Fixed Dose